Effect of Corrosion Damage on the Performance Level of a 25-Year-Old Reinforced Concrete Building. (2012) - Yalciner, Hakan; Sensoy, Serhan; Eren, Ozgur
Abstract : Corrosion is a long-term process resulting in the deterioration of the reinforced concrete (RC) structures. Most of the structural problems observed under the impact of either earthquakes or service loads might occur due to corrosion. Therefore, prediction of the remaining service life of a corroding RC structure plays an important role to prevent serious premature damage. In this study, a corroded, 25-year-old high school building which has been demolished at an earlier time was analyzed as a function of corrosion rate. Bond-slip relationships were taken into account in nonlinear analyses as a function of corrosion rate for different time periods (i.e., non-corroded (t: 0), existing (t: 25) and 50 years after construction); and they were used to ensure the effect of time-dependent slip rotation on the global structural behaviour by modifying the target post-yield stiffness of each structural member. Nonlinear push-over analyses were performed by defining the time-dependent plastic hinge properties as a consequence of corrosion effects. In order to define the performance levels of three different time periods, nonlinear incremental dynamic analyses (IDA) were performed for 20 earthquake ground motion records as a function of corrosion rate. Results showed that bond-slip relationship between concrete and steel is very important in evaluating the non-linear behaviour of corroded RC structures.